2018
DOI: 10.1088/1361-6528/aaae5c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effects of surface stripping ZnO nanosheets

Abstract: ZnO nanosheets are polycrystalline nanostructures that are used in devices including solar cells and gas sensors. However, for efficient and reproducible device operation and contact behaviour the conductivity characteristics must be controlled and surface contaminants removed. Here we use low doses of argon bombardment to remove surface contamination and make reproducible lower resistance contacts. Higher doses strip the surface of the nanosheets altering the contact type from near-ohmic to rectifying by remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Argon bombardment with the cluster modes did not significantly alter the relative intensity or shape of the DLE peak. It should be noted DLE peak of the 10 ke V Ar + 500 sample is slightly higher than the other peaks, however, this is with the range of variance across the sample and is in line with the uncertainty in our previous work and is therefore not consider significant [11]. However, it can be seen from figure 3 that treatment with the monoatomic source causes the DLE peak to reduce relative to the NBE peak, with the more aggressive etch of 5 kV resulting in a reduction in the DLE peak to NBE peak ratio from 40:1 to 18:1.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Argon bombardment with the cluster modes did not significantly alter the relative intensity or shape of the DLE peak. It should be noted DLE peak of the 10 ke V Ar + 500 sample is slightly higher than the other peaks, however, this is with the range of variance across the sample and is in line with the uncertainty in our previous work and is therefore not consider significant [11]. However, it can be seen from figure 3 that treatment with the monoatomic source causes the DLE peak to reduce relative to the NBE peak, with the more aggressive etch of 5 kV resulting in a reduction in the DLE peak to NBE peak ratio from 40:1 to 18:1.…”
Section: Resultssupporting
confidence: 82%
“…In our previous work we attribute the improvement in contact consistence to the removal of adventitious carbon by argon bombardment. [11,12] table 1 shows that the carbon percentage before argon treatment ranged from 16% to 29%, depending on the location on the substrate. The shape and position of the C 1s peak did not shift after argon bombardment, however, from table 1 the quantity of carbon reduced in line with the dose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have observed that chemical passivation of ZnO nanowires with PMMA, Al2O3, aryldiazonium salt or hydrogen plasma, as well as annealing, reduced defects at the surface that cause surface charge and shift the n-type behaviour to intrinsic [5][6][7][8][9][10][11]. Our previous work has used argon bombardment to strip the surface of ZnO nanorods and nanosheets, causing a shift from near-ohmic to rectifying contacts, and suggested a shift from n-type towards p-type caused a reduction in surface defects [12][13][14]. Recent work using X-ray Photoelectron Spectroscopy (XPS) has shown that etching with a monoatomic Ar + beam at 5 keV for 5 minutes causes a shift of 0.3 eV in the valence band, indicating upward band bending [15].…”
Section: Introductionmentioning
confidence: 99%
“…When studying the electronic properties, the lithographic formation of contacts can contaminate the sample, particularly any residual resist [19][20][21]. Direct probe contact to nano-materials instead provides a local, non-destructive and comparably fast technique for electronic transport measurements [22][23][24].…”
Section: Introductionmentioning
confidence: 99%